2016
DOI: 10.1111/1754-9485.12540
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference levels for digital mammography in New South Wales

Abstract: MGD is dependent upon compressed breast thickness and it is recommended that DRL values should be specific to compressed breast thickness and image detector technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…The calculation of MGD in our study followed the methods described by Dance et al 9,12,13 This method calculates MGD using entrance air kerma and three conversion factors that depend on age, CBT, half value layer (HVL), and anode/filter combination. A full explanation of the methodology has been previously described 29 (Figure 1). AGD in our work was calculated by replacing the original c factor values (6 in Figure 1) with Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of MGD in our study followed the methods described by Dance et al 9,12,13 This method calculates MGD using entrance air kerma and three conversion factors that depend on age, CBT, half value layer (HVL), and anode/filter combination. A full explanation of the methodology has been previously described 29 (Figure 1). AGD in our work was calculated by replacing the original c factor values (6 in Figure 1) with Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, international DRLs comparisons were found to be difficult (Suleiman et al, 2015). To overcome these variations and allow comparisons, it was suggested that DRLs should be correlated to the thickness of the compressed breast and equipment specifications (Suleiman et al, 2017).…”
Section: Mammography and Tomosynthesismentioning
confidence: 99%
“…Phantom-based values is a method for evaluation of organ dose conversion coefficient in occupational, medical and environmental radiation protection. DRLs quantity measurements using phantoms are not typically the same as in the clinical environment (Suleiman et al, 2017). This is due to the limitations in variability of real patients' sizes using imaging protocols.…”
Section: Phantom-based Valuesmentioning
confidence: 99%
“…As a relatively large group of specialized professionals, we have the resources to continually collect data and review results to ensure that equipment is not just satisfactory, but optimal; one example of this is the establishment of Diagnostic Reference Levels [45][46][47]. Throughout my career, it has been a privilege to work as part of a multidisciplinary team of dedicated mammography professionals, particularly radiographers and radiologists, who value the knowledge that a physicist brings to the field.…”
Section: The Role Of the Medical Physicistmentioning
confidence: 99%